The Green Economy: How Sustainable Development Can Drive Economic Growth and Prosperity - Irawan, Andri; Supriyanto, Supriyanto (Economics Studies and Banking Journal (DEMAND), 2024)
This research examines the integration of green economic aspects in national development policies, with a focus on environmental education and awareness, investment in green infrastructure, green fiscal and tax policies, as well as the integration of environmental aspects in spatial planning. The research method used was a systematic literature review using the PRISMA approach. The research results show that the integration of green economic aspects can produce long-term economic benefits such as increasing economic competitiveness, reducing environmental and health risks, economic diversification, and improving quality of life. The implications of this research show the importance of environmental education, green infrastructure investment, green fiscal policy, and sustainable spatial planning in supporting the green economy and national development.